Pengaruh Lingkungan Belajar Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPAS kelas IV SD Negeri 230 Palembang - Mayasari, Dona; Yulaini, Erma; Utomo, Budi (Lembaga Bale Literasi, 2025)
This study aims to analyze the influence of the learning environment on students' learning outcomes in the Science and Social Studies (IPAS) subject for fourth-grade students at SD Negeri 230 Palembang. The research employed a quantitative approach with an experimental method, specifically using a True Experimental Design in the form of a Posttest-Only Control Design. The research subjects included two fourth-grade classes from different academic years: 2020/2021 and 2024/2025, each consisting of 28 students. The independent variable in this study is the learning environment, while the dependent variable is students' learning outcomes in the IPAS subject. Learning outcomes were assessed through semester report card scores, and students' perceptions of the learning environment were measured using a questionnaire. The findings revealed that the average report card score for the 2020/2021 class was 81.29, which is categorized as